Usulan Tata Letak Group Technology Pada Fasilitas Workshop PT. Sarana Energi Investama - Gunawan, Sebastian; Hidayat, Trifenaus Prabu; Sugioko, Andre (Universitas Mercu Buana, 2023)
PT Sarana Energi Investama operates as an industry in the field of electrical components. Some of the products produced by PT Sarana Energi Investama include LVMDP panels, sub-distribution panels, Lighting panel, Emergency panel, Elevator panels, and others. In this case, the layout owned by PT Sarana Energi Investama is still non-standard in nature and was placed without taking into account the flow of production as well as the frequency and relations between production facilities. In this case, research was conducted regarding the design of the facility layout at the workshop facility owned by PT Sarana Energi Investama using the group technology layout. Group technology layout is considered one of the methods that can be used to design layouts in an effective, efficient, and flexible manner for customized product types and is able to overcome production constraints when the quantity of demand fluctuates. In the study, calculations were carried out using routing sheets, calculating the frequency of transfers, determining relationships between facilities, using rank-order clustering algorithms to design group technology layouts, as well as designing intracellular and overall facility layouts. Based on this research, using the proposed layout can increase the efficiency of moving distances by 40.74%, moving time by 31.25%, and material handling costs by 31.25% within a month.